If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1) = 9x + -8 Reorder the terms: (1 + x) = 9x + -8 Remove parenthesis around (1 + x) 1 + x = 9x + -8 Reorder the terms: 1 + x = -8 + 9x Solving 1 + x = -8 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 1 + x + -9x = -8 + 9x + -9x Combine like terms: x + -9x = -8x 1 + -8x = -8 + 9x + -9x Combine like terms: 9x + -9x = 0 1 + -8x = -8 + 0 1 + -8x = -8 Add '-1' to each side of the equation. 1 + -1 + -8x = -8 + -1 Combine like terms: 1 + -1 = 0 0 + -8x = -8 + -1 -8x = -8 + -1 Combine like terms: -8 + -1 = -9 -8x = -9 Divide each side by '-8'. x = 1.125 Simplifying x = 1.125
| -7d=27-(3-d) | | 5(x+y)+6x= | | 5m+5=15 | | 8x^2y^2-44xy+48=0 | | 3(x+7)=-2 | | 7t+6=11t-4 | | x+24-9=-8 | | 5x+9+5x=99 | | 6x^2y^2+5xy-6=0 | | 5x^2+28x+15=0 | | 8x-4=3x-9 | | 12-2(g-3)=g | | -7v+19=3(v+3) | | 4m^2-8mn+3n^2=0 | | ln(2x+1)=10 | | 6x^4-8x^2-5=0 | | 7(3a-5b+6)= | | 6x+12=2x+14 | | 7(x+1)=4[x-(3x-x)] | | 6x^2-4=-5x | | 7x-4x=27 | | 13x-4x=23 | | x=70y+200 | | x=70*x+200 | | x=70x+200 | | 5p^2q^2-7pq-6=0 | | 2x=20+300 | | 0=2x^3-6x^2+5x-15 | | -1.8=9.5+a | | 0=2x^4-6x^3+5x^2-15x | | 12=w-5.8 | | 0=2x^3-3x^2+5x-15 |